Reliminary Antibacterial and Phytochemical Evaluation of Dryopteris Cochleata (D.DON) C.CHR - Toji Thomas (Journal of Global Pharma Technology, 2011)
Ryopteris cochleata Dryopteridaceae is one of the important plants of traditional systems of medicine. Fronds (leaves) of Dryopteris cochleata were evaluated for its antibacterial potential and phytochemical contents in various solvent extracts in increasing polarity towards pathogenic bacterial species. Antibacterial activity was tested by disc diffusion method. Petroleum ether, acetone, methanol and water extracts of Dryopteris cochleata were tested for antibacterial activity towards some pathogenic bacterial strains. Both acetone and methanol extracts exhibited antibacterial activity; maximum activity was shown by acetone extract compared to others. Antibacterial activity was confirmed by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). MIC and MBC values of acetone extract of 12.5mg/ml and 25mg/ml were observed towards Staphyococcus albus while MIC and MBC values of 25mg/ml and 50mg/ml were observed towards Pseudomonas aeruginosa. Flavonoids, phenols, steroids were detected in acetone and methanol extracts. The study proves that Dryopteris cochleata possesses antibacterial principles, soluble in acetone, which hinder the growth and multiplication of some multidrug resistant bacterial strains. Keywords: Dryopteris cochleata, yopteridaceae, Tibacterial, Dsc diffusion.